The Dynamical Emergence of Biology From Physics: Branching Causation via Biomolecules - Ellis, George F. R.; Kopel, Jonathan (Frontiers in Physiology, 2019)
Biology dffers fundamentally from the physics that underlies it. This paper pro- poses that the essential difference is that while physics at its fundamental level is Hamiltonian, in biology, once life has come into existence, causation of a contextual branching nature occurs at every level of the hierarchy of emergence at each time. The key feature allowing this to happen is the way biomolecules such as voltage-gated ion channels can act to enable branching logic to arise from the underlying physics, despite that physics per se being of a deterministic nature. Much randomness occurs at the molecular level, which enables higher level functions to select lower level out- comes according to higher level needs. Intelligent causation occurs when organisms engage in deduction, enabling prediction and planning. This is possible because ion channels enable action potentials to propagate in axons. They further key feature is that such branching biological behaviour acts down to cause the underlying physical interactions to also exhibit a contextual branching behaviour.